Chimpanzees in context a comparative perspective on chimpanzee behavior, cognition, conservation, and welfare - Hopper, Lydia M.; Ross, Stephen R.; Goodall, Jane, 1934- (The University of Chicago Press, 2020)
"The study of the chimpanzee, the human's closest relative, has led scientists to exciting discoveries about evolution, behavior, and cognition over the past half century. In this book, both young and veteran scholars take a fascinating comparative approach to the culture, behavior, and cognition of both wild and captive chimpanzees. By seeking new perspectives in how the chimpanzee compares to other species, the scientists featured in this book offer a richer understanding of the ways in which chimpanzees' unique experiences shape their behavior. They also demonstrate how different methodologies provide different insights, how various cultural experiences influence our perspectives of chimpanzees, and how different ecologies in which chimpanzees live affect how they express themselves. After a foreword by Jane Goodall the book follows sections that examine chimp life histories and developmental milestones, behavior, methods of study, animal communication, cooperation and communication, tool use, chimpanzee care, and chimpanzee conservation. Collectively, these chapters remind us of the importance of considering the social, ecological, and cognitive context of chimpanzee behavior, and how these contexts shape our interpretation of our understanding of chimpanzees. Only by leveraging these powerful perspectives do we stand a chance at improving how we understand, care for, and protect this species"--